2007
DOI: 10.1073/pnas.0705701104
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage-site recognition by lysine conjugates

Abstract: Simple lysine conjugates are capable of selective DNA damage at sites approximating a variety of naturally occurring DNA-damage patterns. This process transforms single-strand DNA cleavage into double-strand cleavage with a potential impact on gene and cancer therapy or on the design of DNA constructs that require disassembly at a specific location. This study constitutes an example of DNA damage site recognition by molecules that are two orders of magnitude smaller than DNA-processing enzymes and presents a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…This observation suggested that these photocleavers may damage DNA through base alkylation as well. Subsequent work confirmed that compound 4 in capable of localized DNA cleavage and the damage does not dissipate through hole hopping when the same single G site is chosen as a target using phosphate-lysine recognition 37. Furthermore, we also observed frank cleavage in 5’-(AATT) n GG(AT) m GG(AAATTT) l -3’ oligomers.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…This observation suggested that these photocleavers may damage DNA through base alkylation as well. Subsequent work confirmed that compound 4 in capable of localized DNA cleavage and the damage does not dissipate through hole hopping when the same single G site is chosen as a target using phosphate-lysine recognition 37. Furthermore, we also observed frank cleavage in 5’-(AATT) n GG(AT) m GG(AAATTT) l -3’ oligomers.…”
Section: Resultssupporting
confidence: 73%
“…Several explanations are possible. For example, the remarkable ability of lysine to recognize a nick in DNA and facilitate a break of the complementary strand (the ss→ds cleavage conversion) discovered in our previous work37 may play some role in the high efficiency of the ds cleavage. However, the enhancement of this type of cleavage at the lower pH is an unprecedented phenomenon.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Not only do the positively charged amino acid residues allow to modulate binding with an anionic target such as DNA but they also allow to control photophysics of the enediyne chromophore via pH‐gated intramolecular photoinduced electron transfer (PET). These conjugates are able to selectively cleave at G‐sites flanking A‐T tracks , convert nicked (ss) DNA into linear (ds) DNA and induce intracellular DNA damage . Further modifications of the DNA binding and pH‐regulating amino acid part of the hybrid molecules lead to highly efficient ds DNA photocleavage .…”
Section: Introductionmentioning
confidence: 99%
“…This dramatic increase of ds DNA cleavage at the lower pH renders these molecules more efficient ds DNA cleavers than calicheamicine under the conditions suitable for selective targeting of acidic cancer tissues ( Figure 2(a) ). We also found that the C-lysine conjugates bind selectively to nicks and gaps in a DNA duplex and, upon photochemical activation, transform the easily repairable ss-DNA damage into much more therapeutically important ds-DNA damage [ 20 ] ( Figure 2(b) ).…”
Section: Introductionmentioning
confidence: 99%